DAMPAK KERUSAKAN LINGKUNGAN HIDUP AKIBAT PERTAMBANGAN BATU GUNUNG DI KECAMATAN SUNGAI KUNJANG KOTA SAMARINDA BERDASARKAN UNDANG-UNDANG NO 32 TAHUN 2009 - Erni Erni (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACT            Environmental Damage Due to Mining Stone Mountain in Sungai Kunjang Samarinda. Guided by the Supervisor I Kunti Widayati, SH, M. Hum. and Supervisor II Isnawati, S.H, M. Hum.The problem in this paper is what is the impact of the damage caused by mining in Stone Mountain Road MT. Newer haryono Sungai Karang village Kunjang Samarinda and legal efforts undertaken by the municipality samantha according to Law Number 32 Year 2009 on PPLH.            Related to the results of the study showed that there are still many illegal stone mining mountain or do not have permission, so that many of the adverse impact directly to the affected communities. There is still a constraint in terms of the government's oversight. We recommend in this case about the impact of the mountain rock mining damage, should the Environment Agency (BLH) Samarinda be included. In the environmental impact control the government should Samarinda along with relevant agencies competent in this case the Environment Agency Samarinda expected to be proactive and more stringent in terms of supervision in order to minimize environmental damage from coal mining mountain is bad. From the research conducted it can be concluded that the lack of direct supervision and strict sanctions to the perpetrators of environmental destruction.